Implementation of Artificial Intelligence Policy in the Field of Livestock and Dairy Farm - Chimakurthi, Venkata Naga Satya Surendra (American Journal of Trade and Policy, 2019)
Artificial intelligence is changing each and every field of the modern world and livestock is not any exception. It is greatly expected that this modern technology has the potential to bring a breakthrough in the field of livestock through combining biological information with technological advancement. Modern farms with the implementation of AI techniques are showing exceptional growth as they have improved efficiency in terms of livestock production and minimized the physical labor as well as the labor cost. Thus this sector has become more significant in world GDP. The present study is intended to highlight the principal benefits provided by AI techniques including robots, drones, and 3D printing.  Through this research, readers can get a better idea about applications of AI, its benefits and disadvantages in the field of dairy farming and livestock. It will also encourage fellow researchers to conduct such research in the future.
Keywords: Artificial Intelligence; Smart Farming; Modern Livestock; AI Policy